Free vibration analysis of functionally graded shell panels with various geometric shapes in thermal environment - Huan, Duong Thanh; Quoc, Tran Huu; Tu, Tran Minh (Vietnam Journal of Mechanics, 2018)
This paper presents free vibration analysis of functionally graded materials (FGMs) shell panels with various geometric shapes in thermal environments. The shell panels are made from a mixture of metal and ceramic. Material properties are assumed to be temperature-dependent and graded in the thickness direction according to a power law function. A formulation of eight-nodded middle surface shell elements based on Reissner-Mindlin assumptions is developed for modeling FGM shell panels under the effect of temperature, which changes nonlinearly across the thickness. Numerical results obtained by the proposed model are in good agreement with those available in the literature. The effects of geometric properties, material composition, boundary conditions and temperature on the natural frequencies are investigated.